LEGAL PROTECTION OF INTERIOR DESIGN IN INDUSTRIAL DESIGN INTELLECTUAL PROPERTY RIGHTS - Ida Ayu Sadnyini; I Gede Putu Agus Wistama Putra; A.A.A.Ngurah Sri Rahayu Gorda; A.A.A. Ngurah Tini Rusmini Gorda (Warmadewa Press, 2021)
Intellectual property is creativity that results from human thought in order to meet the needs and welfare of human life. Currently, IPR issues are widely discussed in the context of international issues. IPR includes two parts, namely Copyrights and Industrial Property Rights. Industrial property rights include patents, industrial designs, integrated circuits layout designs, trade secrets, geographic indications, trademarks and plant variety protection (PVP). Interior design is part of industrial design. Interior design has experienced significant developments in recent years, including in Indonesia. Problems that arises is plagiarisms done by imitating or using the